The missing link in gravitational-wave astronomy: discoveries waiting in the decihertz range. (7th October 2020) - Sedda, Manuel Arca; Berry, Christopher P L; Jani, Karan; Amaro-Seoane, Pau; Auclair, Pierre; Baird, Jonathon; Baker, Tessa; Berti, Emanuele; Breivik, Katelyn; Burrows, Adam; Caprini, Chiara; Chen, Xian; et al.
Abstract: The gravitational-wave astronomical revolution began in 2015 with LIGO's observation of the coalescence of two stellar-mass black holes. Over the coming decades, ground-based detectors like laser interferometer gravitational-wave observatory (LIGO), Virgo and KAGRA will extend their reach, discovering thousands of stellar-mass binaries. In the 2030s, the space-based laser interferometer space antenna (LISA) will enable gravitational-wave observations of the massive black holes in galactic centres. Between ground-based observatories and LISA lies the unexplored dHz gravitational-wave frequency band. Here, we show the potential of a decihertz observatory (DO) which could cover this band, and complement discoveries made by other gravitational-wave observatories. The dHz range is uniquely suited to observation of intermediate-mass (∼10 2 –10 4 M ⊙ ) black holes, which may form the missing link between stellar-mass and massive black holes, offering an opportunity to measure their properties. DOs will be able to detect stellar-mass binaries days to years before they merge and are observed by ground-based detectors, providing early warning of nearby binary neutron star mergers, and enabling measurements of the eccentricity of binary black holes, providing revealing insights into their formation. Observing dHz gravitational-waves also opens the possibility of testing fundamental physics in a new laboratory, permitting unique tests of general relativity (GR) and the standard model of particle physics. Overall, a DO would answer outstanding questions about how black holes form and evolve across cosmic time, open new avenues for multimessenger astronomy, and advance our understanding of gravitation, particle physics and cosmology.